Determinant factors for loss to follow-up in drug-resistant tuberculosis patients: the importance of psycho-social and economic aspects - Soedarsono Soedarsono (BMC, 2021)
Abstract Background Drug-resistant tuberculosis (DR-TB) is the barrier for global TB elimination efforts with a lower treatment success rate. Loss to follow-up (LTFU) in DR-TB is a serious problem, causes mortality and morbidity for patients, and leads to wide spreading of DR-TB to their family and the wider community, as well as wasting health resources. Prevention and management of LTFU is crucial to reduce mortality, prevent further spread of DR-TB, and inhibit the development and transmission of more extensively drug-resistant strains of bacteria. A study about the factors associated with loss to follow-up is needed to develop appropriate strategies to prevent DR-TB patients become loss to follow-up. This study was conducted to identify the factors correlated with loss to follow-up in DR-TB patients, using questionnaires from the point of view of patients. Methods An observational study with a cross-sectional design was conducted. Study subjects were all DR-TB patients who have declared as treatment success and loss to follow-up from DR-TB treatment. A structured questionnaire was used to collect information by interviewing the subjects as respondents. Obtained data were analyzed potential factors correlated with loss to follow-up in DR-TB patients. Results A total of 280 subjects were included in this study. Sex, working status, income, and body mass index showed a significant difference between treatment success and loss to follow-up DR-TB patients with p-value of 0.013, 0.010, 0.007, and 0.006, respectively. In regression analysis, factors correlated with increased LTFU were negative attitude towards treatment (OR = 1.2; 95% CI = 1.1–1.3), limitation of social support (OR = 1.1; 95% CI = 1.0–1.2), dissatisfaction with health service (OR = 2.1; 95% CI = 1.5–3.0)), and limitation of economic status (OR = 1.1; 95% CI = 1.0–1.2)). Conclusions Male patients, jobless, non-regular employee, lower income, and underweight BMI were found in higher proportion in LTFU patients. Negative attitude towards treatment, limitation of social support, dissatisfaction with health service, and limitation of economic status are factors correlated with increased LTFU in DR-TB patients. Non-compliance to treatment is complex, we suggest that the involvement and support from the combination of health ministry, labor and employment ministry, and social ministry may help to resolve the complex problems of LTFU in DR-TB patients.